2005
DOI: 10.2193/0022-541x(2005)069<0277:gbdiaa>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Grizzly Bear Demographics in and Around Banff National Park and Kananaskis Country, Alberta

Abstract: The area in and around Banff National Park (BNP) in southwestern Alberta, Canada, is 1 of the most heavily used and developed areas where grizzly bears (Ursus arctos) still exist. During 1994-2002, we radiomarked and monitored 37 female and 34 male bears in this area to estimate rates of survival, reproduction, and population growth. Annual survival rates of bears other than dependent young averaged 95% for females and 81-85% for males. Although this area was largely unhunted, humans caused 75% of female morta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
118
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 140 publications
(136 citation statements)
references
References 60 publications
17
118
0
1
Order By: Relevance
“…These simulated results are consistent with the empirical data reported by Garshelis et al (2005). They used the unbiased M4 method and reported an unexpectedly low Mx compared to other North American grizzly bear populations (0.24 vs. 0.32).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…These simulated results are consistent with the empirical data reported by Garshelis et al (2005). They used the unbiased M4 method and reported an unexpectedly low Mx compared to other North American grizzly bear populations (0.24 vs. 0.32).…”
Section: Discussionsupporting
confidence: 88%
“…They attributed their relatively low value of Mx due to some combination of real biological differences and/or bias in the other studies. We concur with Garshelis et al (2005) that they found an unexpectedly small Mx and that the differences in estimated Mx were substantial-but the evidence presented here suggests that the main cause may be bias in other studies using the biased method M3 (Eberhardt et al 1994;Hovey and McLellan 1996;Miller 1997), not an abnormally small Mx in their study area. We suspect that estimates of Mx reported in the literature using method M3, including our own previous work , may be biased overestimates.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Benn and Herrero (2005) found that 119 of 131 recorded grizzly bear mortalities in Banff National Park and the adjoining Yoho National Park in the period 1971-1998 were due to human-related causes, and that ''all 95 humancaused mortalities with known accurate locations were within 500 m of roads or 200 m of trails' ' (p. 63). Intensive management and frequent interventions to move or protect individual bears have improved the survival rate for grizzlies in Banff National Park in recent years, but humans are still the primary cause of death (Garshelis et al 2005a).…”
Section: The Context: People and Grizzly Bears In Banff National Parkmentioning
confidence: 99%